On The Correlation Factor Between Key Characteristics Of Efficient Driving And Safe Driving - Wong, Kah Jian (Universiti Sains Malaysia, 2017)
In this research, a few approaches were done on the correlation factor between key characteristics of efficient driving and safe driving. The approaching method was basically qualitative research method and quantitative research method. This research mainly was to indicate the relationship between safe driving and efficient driving. It attempts to give correct motivation on safe driving towards efficient driving, because some of the circumstances efficient driving may not be safe, and sometimes efficient driving can lead to safety. During the progress of the research, the main driving characteristics were listed and analysed on the relationship with safety and efficiency. However, the level of efficiency and level of safety on each of every driving characteristics does not have a standard way to measure like height and weight is measured in centimetre and kilogram. In order to put safe driving and efficient driving in to calculation, each of every driving characteristics were ranked from the safest to most dangerous and the most efficient to the most inefficient. The ranking of each of every characteristics on safety were based on the chance of the driving characteristics leads to accident and the seriousness of the accident if the accident happened due to the practice of the driving characteristics. The ranking for each of every driving characteristics on efficient driving were measured by the factor of the level of idling, acceleration, braking and speed. Weightage scales were given to the ranking of safe driving and efficient driving where the magnitude of the safety or efficiency was represented by the numerical values of the weightage. Thus, calculation on the correlation factor could be conducted by the mathematical formula. This research had made several approaches to obtain a numerical values of correlation factor between key characteristics of efficient driving and safe driving which initially both of the safety level and efficiency level on the driving characteristics were non-measurable. The correlation factor between key characteristics of efficient driving and safe driving was overall positive and significant.